Innovative Solution for Contradictions of Waste Handling in Disassembly Process Using TRIZ Method - Muqimuddin Muqimuddin; Yemima Elza Desideria Desideria; Faishal Arham Pratikno (G-Tech: Jurnal Teknologi Terapan, 2024)
The disassembly phase in remanufacturing currently takes an average of 8 days, surpassing the standard of 7 days due to non-value-added activities, as known as waste. Although efforts to handle this issue have been made, they have introduced new challenges, particularly time waste in system adjustments. This study addresses the problem by employing TRIZ and Root Conflict Analysis (RCA+) methods to identify contradictions and propose innovative solutions to minimize waste. Findings reveal a 25% waste activity, with waiting activities contributing to 19% of the total. The research identifies 5 contradictions, each having both negative and positive impacts on the disassembly process. Proposed solutions involve implementing Magnetic Particle Testing or Ultrasonic Testing, organizing tiered boxes, offering understanding and inspection supervision to mechanics, utilizing a variety of wrench sizes, and developing a checklist for disassembly stages based on the sequence of main components.